Pengembangan Modul Konsep Mol Berbasis Inkuiri Terstruktur dengan Penekanan Pada Interkoneksi Tiga Level Representasi Kimia Untuk Kelas X SMA - Randa Sagita; Fajriah Azra; Minda Azhar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The research has created the module of mole concept based on structured inquiry with interconnection of multiple representation and determined the validity and practicality of the module. The research type was Research and Development (R&D). The development model was 4-D models that consist of four steps: define, design, develop, and disseminate. The research was limited on develop step. The instrument of the research was questionnaire form that consist of validity and practicality sheets. The module was validated by 5 validators. Practicality module was tested by 2 chemistry teachers and 28 students of grade XI MIA 5 at SMAN 4 of Padang. Validity and practicality data were analysed by using the kappa Cohen formula. The moment kappa average of 5 validators was 0,95 with highest validity category. The moment kappa average of teachers and students were 0,89 and 0,91 praticality with high category. The result of the research showed that the module of mole concept based on structured inquiry with interconnection of macro, submicro, and symbolic representation was valid and practice to be used on the learning chemistry